Effect of Work-Life Balance and Employee Wellbeing on Generation Z Employee Performance in the Era of Hybrid Working - Ruli Haris; Dita Aulia; Muhammad Zeinny Hasbunallah Sasmita; Agus Susanto; Teul Panda Banjal; Femy Novalia; Harun Indra Kusuma; Muhammad Rizki Zul Hisyam; Yakup Hermansyah (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study examines the effects of work-life balance and employee wellbeing on the performance of Generation Z employees in the hybrid working era. Methodology: Using a quantitative design, data were gathered from 120 Gen Z employees in Jabodetabek who worked under hybrid arrangements and were analysed using multiple linear regression in SPSS 26. Results: Work-life balance (t = 5.930; p < 0.001) and employee wellbeing (t = 5.721; p < 0.001) each had a significant positive effect on performance, and their simultaneous effect was also significant (F = 62.483; p < 0.001). Findings: The model explained 50.8% of the variance in employee performance (Adjusted R² = 0.508). Novelty & Originality: This study integrates work-life balance and employee wellbeing in one model focused specifically on Gen Z employees in a post-pandemic hybrid setting. Conclusions: Organisations should strengthen hybrid working policies that support balance and wellbeing in order to improve Gen Z employee performance. Type of Paper: This paper is a research article.